Featherwork and Divine Chieftainship in Tonga - Herda, Phyllis; Lythberg, Billie (Waka Kuaka, 2014)
Pala tavake were sacred regalia, feather headdresses, reserved for the traditional sacred ruler of Tonga, the Tu‘i Tonga. Recently a fanned feathered headdress whose materials and construction are commensurate with 18th century Tongan objects was uncovered at Madrid’s Museo de América. This paper considers the feather headdress located in Madrid, its probable historical context and connections – both Tongan and Spanish. In addition we discuss the association of pala tavake with the Tu‘i Tonga, the sacred ruler of Tonga, and the changing nature of the title in the late 18th century.